Differential Subordination Results for Analytic Functions in the Upper Half-Plane - Huo Tang; M. K. Aouf; Guan-Tie Deng; Shu-Hai Li (Abstract and Applied Analysis)
There are many articles in the literature dealing with differential subordination problems for analytic functions in the unit disk, and only a few articles deal with the above problems in the upper half-plane. In this paper, we aim to derive several differential subordination results for analytic functions in the upper half-plane by investigating certain suitable classes of admissible functions. Some useful consequences of our main results are also pointed out.